Staying together: people-wildlife relationship in the Amboseli Ecosystem, southern Kenya - Pinho, J.R. de; Ellis, J. (GL-CRSP, 2009)
The relationship of Maasai pastoralists to the wild animals with which they share land and resources has been described as “harmonious” and “tolerant.” This research brief describes a study of local attitudes towards wildlife within Maasai communities of the Amboseli ecosystem. This study investigates the multiple dimensions of the relationship between pastoralists and wild animals in three Maasai group ranches in the Kajiado District of southeastern Kenya, under present conditions of demographic, cultural and socio-economic changes. Preliminary results reveal that despite a high perceived level of conflict between people and wild animals and the perceived lack of wildlife-based economic benefits, attitudes towards wild animals are generally positive, even though they are motivated by different factors, especially across age groups. The co-existence of people and wildlife in the Amboseli ecosystem is multifaceted and goes beyond assumptions that Maasai live in harmony with wildlife. Final research results will contribute a multi-layered and sensitive picture of the co-existence of humans, livestock and wild animals in the Amboseli ecosystem to guide policy-makers in smart planning and adaptive policies that integrate conservation and livelihoods.